FILSAFAT MANUSIA : SEBUAH KAJIAN TEKS DAN KONTEKS DALAM MEMAHAMI HAKIKAT DIRI - I Gusti Made Widya Sena (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Humans actually have two bodies when born in this world, namely the material body and spiritual body. The material body is a form of physical-physical form that is crude and serves to carry out all forms of desires from the five senses, the respiratory system, the digestive system, muscles, neural networks, blood circulation and others. Whereas the spiritual body is a psychic body that is subtle and consists of a causal body (buddhi), a supra causal body (subtle ego) and atman. Born as a human being is the ultimate happiness in life because by being born into the world, a person is given the opportunity in his life to achieve the essence of himself by doing and increasing karma, bhakti, jnana to finally achieve contemplation by realizing the nature of self and atman in his body. This is what gives happiness to be born into a human being compared to being a creature in the world